2019
DOI: 10.1371/journal.pone.0215211
|View full text |Cite
|
Sign up to set email alerts
|

I thought I saw a pussy cat: Portrayal of wild cats in friendly interactions with humans distorts perceptions and encourages interactions with wild cat species

Abstract: Most people lack the opportunity to see non-domesticated animals in the wild. Consequently, people’s perception of wild animals is based on what they see on (social) media. The way in which (social) media portrays non-domesticated animals determines our perception of and behaviour to these animals. People like to interact with animals, which is why venues which offer the opportunity to interact with non-domesticated animals are popular wildlife tourist attractions (WTAs). However, these WTAs more often than no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
(90 reference statements)
1
19
0
Order By: Relevance
“…The Kangaroo did not receive significantly different levels of agreement compared to the snake, which could suggest that charismatic megafauna (large mammals with high public popularity) are simply less likely to be considered good pets. This theory is further supported by Van der Meer, Eckman, and Bockhart [38], who saw similar trends when showing images of humans and big cats, and Spooner and Stride [39], who suggest similar findings with images of large mammals. Again, this may be due to the increased emotional connection that humans seem to have with large mammals, which may foster the belief that such animals belong in their natural habitat to increase their welfare and happiness, and thus should not be owned [63,74].…”
Section: The Animal Would Make a Good Petmentioning
confidence: 63%
See 1 more Smart Citation
“…The Kangaroo did not receive significantly different levels of agreement compared to the snake, which could suggest that charismatic megafauna (large mammals with high public popularity) are simply less likely to be considered good pets. This theory is further supported by Van der Meer, Eckman, and Bockhart [38], who saw similar trends when showing images of humans and big cats, and Spooner and Stride [39], who suggest similar findings with images of large mammals. Again, this may be due to the increased emotional connection that humans seem to have with large mammals, which may foster the belief that such animals belong in their natural habitat to increase their welfare and happiness, and thus should not be owned [63,74].…”
Section: The Animal Would Make a Good Petmentioning
confidence: 63%
“…We suggest that the presence and distance of a human from an animal in such images may play a strong role in perceptions of ownership or companionship with the Featured Animal, either by highlighting the dominance of humans over wildlife or by increasing perceptions that such behaviour is appropriate. Both suggestions are supported by Siriwat and Nijman [71], Otsuka and Yamakoshi [29], Van der Meer, Bockhart, and Eckman [38], and Stride [39], who have all found that imagery of humans and animals together on social media increases expectations that viewers can approach, touch, and own animals that are not considered domestic. As such images increase in popularity and number, the theories of social norms [42] and repeat messaging [72] suggest that these behaviours may increase in number and severity, as seen by Otsuka and Yamakoshi [29].…”
Section: The Animal Would Make a Good Petmentioning
confidence: 92%
“…Moorhouse et al [ 2 ] scored 24 types of wildlife tourist attractions and deemed only six to have positive conservation and welfare impacts. van der Meer, Botman and Eckhardt [ 12 ] concurred and considered most wildlife tourist attractions to be about making a profit. Essen, Lindsjö and Berg [ 1 ] go so far as to describe animals within animal-based tourism as “laborers in a global capitalist economy where they are conscripted into the service of the tourism industry”.…”
Section: Introductionmentioning
confidence: 99%
“…Often such images are of celebrities, TV presenters and researchers. Such imagery normalizes close contact, exacerbates any lack of societal risk response and diminishes the perception that human behaviours can cause risk [ Van der Meer et al, 2019;Lenzi et al, 2020;Thomas-Walters et al, 2020].…”
Section: Discussionmentioning
confidence: 99%